Risk factors for recurrent admissions with diabetic ketoacidosis: a case–control observational study. Issue 4 (7th December 2015) - Cooper, H.; Tekiteki, A.; Khanolkar, M.; Braatvedt, G.
Abstract: Aim: To perform a detailed analysis of patients with recurrent diabetic ketoacidosis admissions in order to establish risk factors for readmission. Methods: The medical records of all adults and young people (> 15 years) with Type 1 diabetes admitted to Auckland City Hospital over a 15‐year period from 1997 to 2011 with a primary diagnosis of ketoacidosis were analysed. Patients readmitted with ketoacidosis within 5 years of their index admission were identified and compared with patients without ketoacidosis readmission who were matched for age, gender, ethnicity and duration of diabetes. Results: A total of 268 patients accounted for a total of 412 admissions. In all, 58 patients had more than one admission for diabetic ketoacidosis during this period. Of these, 40 patients readmitted with diabetic ketoacidosis were compared with matched control subjects ( n = 40) who had only one admission for diabetic ketoacidosis. The mean ± sd age of the cohort was 31 ± 12 years. The readmission group had more severe diabetic ketoacidosis and poorer glycaemic control. Alcohol abuse was commonly noted in both groups, with insulin dose omission being the main contributor to the development of ketoacidosis. Both groups had high rates of clinic non‐attendance. There were no other differences noted between the groups. Conclusion: When patients with recurrent diabetic ketoacidosis were matched for age, duration of diabetes, gender and ethnicity with patients who had only one admission for diabetic ketoacidosis, few differences were noted. This makes designing intervention strategies to reduce readmission with diabetic ketoacidosis difficult. What's new?: Long‐term cohort studies at Auckland Hospital have shown a persistently high rate of readmission of patients with DKA. This case–control study compared various bio‐chemical, clinical and social variables of patients admitted with DKA to ascertain predictors of recurrence. It found few differences between the readmitted and control groups, who had been matched for age, gender, ethnicity and duration of diabetes. This highlights the difficulty in identifying who is at risk of recurrent DKA.